Cell‐derived micro‐environment helps dental pulp stem cells promote dental pulp regeneration. (25th July 2017) - Zhang, Xuexin; Li, Hui; Sun, Jingjing; Luo, Xiangyou; Yang, Hefeng; Xie, Li; Yang, Bo; Guo, Weihua; Tian, Weidong
Abstract: Objectives: The function of the dental pulp is closely connected to the extracellular matrix (ECM) structure, and ECM has received significant attention due to its biological functions for regulating cells. As such, the interaction between the ECM niche and cells is worth exploring for potential clinical uses. Materials and methods: In this study, dental pulp stem cell (DPSC)‐derived ECM (DPM) was prepared through cell culture and decellularization to function as the cell niche, and changes in DPSC behaviour and histological analysis of dental pulp tissue regeneration were evaluated following the DPM culture. DPM promoted the replication of DPSCs and exhibited retention of their mineralization. Then, the DPM‐based culture strategy under odontogenic culture medium was further investigated, and the mineralization‐related markers showed that DPSCs were regulated towards odontogenic differentiation. Dental pulp‐like tissue with well‐arranged ECM was harvested after a 2‐month subcutaneous implantation in nude mice with DPM application. Additionally, DPSCs cultured on the plastic culture surface showed the up‐regulation of mineralization makers in vitro, but there was a disorder in matrix formation and mineralization when the cells were cultured in vivo. Results and Conclusions: DPM‐based cultivation could serve as a cell niche and modulate DPSC behaviour, and this method also provided an alternative to harvest tissue‐specific ECM and provided a strategy for ECM‐cell interaction.